Peningkatan Nilai-Nilai Spiritualitas Melalui Pembiasaan Membaca Surat Pendek Sebelum Pembelajaran di SDN 4 Wagir Lor - Yudi Dermawan; Abdah Munfaridatus Sholihah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to instill Islamic spiritual values through the habituation of reciting short surahs before teaching and learning activities at SDN 4 Wagir Lor. This practice is designed to strengthen students’ faith, piety, worship discipline, and noble character, thereby shaping a religious character from an early age. The research employed a descriptive qualitative method with the ABCD (Audience, Behavior, Condition, Degree) approach, with data collected through observation, interviews, and documentation involving the principal, teachers, and students. The findings show that the activity of reciting short surahs is carried out every morning under the guidance of teachers using the Ummi method, with students taking turns leading the recitation. This habituation effectively cultivates spiritual values, enhances understanding of Qur’anic meanings, and builds discipline in worship. Supporting factors include teacher supervision, student awareness, school facilities, a conducive environment, and parental support. However, challenges remain, such as differences in students’ backgrounds, limited Qur’anic reading ability, tardiness, and absenteeism. In conclusion, the habituation of reciting short surahs at SDN 4 Wagir Lor has proven to be an effective model of Islamic spirituality-based character education that is relevant to elementary schools, and it has the potential to inspire other educational institutions in fostering a generation that is faithful, pious, and of noble character